Production and reproduction performance of cattle of irrigated and rainfed areas of Visakhapatnam district of Andhra Pradesh (Indian Journal of Animal Production and Management, 2024)
A study was conducted to assess the production and reproduction performance of cattle in irrigated and  rainfed areas of Visakhapatnam district of Andhra Pradesh. The data pertaining to the animals of 200 dairy  farmers from 50 different villages were collected by using a pretested questionnaire through personal  interview and the data were analysed. The average age at first calving of graded Murrah buffaloes was  significantly (P≤.01) lower in irrigated area than that in rainfed area. The mean lactation milk yield and  lactation length of graded Murrah buffaloes was significantly (P≤.01) higher in irrigated area than that  in rainfed area. There was no significant difference in the peak yield and dry period of graded Murrah  buffaloes between irrigated and rainfed areas. The mean age at first calving of Jersey crossbred cows was  significantly (P≤.01) lower in irrigated area than that in rainfed area. There was no significant difference  in the service period, calving interval, peak yield, lactation milk yield, lactation length and dry period of  Jersey crossbred cows between irrigated and rainfed areas.
Keywords: Cattle; Irrigated; Production and reproduction performance; Rainfed